Multimedia engine basic - Cambridge Research Group Ltd. (New Jersey : Shopware, 1997)
This multimedia program explores engine basics including areas of crankshafts, flywheels and cumshafts, valves, pistons, rings, pins, carburetors and fuel injection
Keywords: Automobiles -- Motors -- Design and construction; Engines